Apoyo social percibido e ideación suicida en pacientes de la Unidad de Atención Integral a personas viviendo con VIH-Sida del Hospital General Isidro Ayora, Loja - Ríos Herrera, Andrety Anahí (2020)
Human immunodeficiency virus (HIV) in addition to carry the social stigma that makes it difficult for the patient to adapt to the illness, it can cause as many psychological consequences as other chronic diseases that are fatal and incurable, generating negative emotional responses that can trigger suicidal attempts and ideations especially when people do not have enough strong support networks. For this reason, the present study sought to determine the existence of the relationship between perceived Social Support and Suicidal Ideation in patients with HIV-AIDS. For the development of the research, a descriptive - correlational design with a cross-section was executed, in which 186 patients from the Integral Care Unit for People Living with HIV-AIDS from the Isidro Ayora Hospital in the city of Loja participated. The reagents used were: Informed Consent, Standardized Questionnaire of the Study of Medical Support of Social Support and Beck's Suicidal Ideation Scale. Through the results a negative and statistically significant correlation was identified by determining an inversely proportional relationship since the greater social support there will be less suicidal ideation, likewise, the less social support there will be a greater index of suicidal ideation. Based on the data obtained, an intervention plan was designed, based on psychoeducation focused on the incidence of social support and suicide prevention in patients of the Comprehensive Care Unit for People Living with HIV-AIDS at Isidro Ayora City Hospital from Loja. Keywords: HIV, AIDS, social support, suicidal ideation, depression, chronic disease.